1981
DOI: 10.1111/j.1471-4159.1981.tb06316.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ouabain on the Release of [14C]Acetylcholine and Other Substances from Synaptosomes

Abstract: The effect of ouabain and dihydroouabain on Na+‐K+ ATPase, 86Rb uptake and the release of [14C]ACh (acetylcholine) from synaptosomal preparations of guinea pigs was compared. At low concentrations of glycoside (<50 μm) there was a good correlation between the potency of ouabain and of dihydroouabain in inhibiting Na+‐K+ ATPase and in causing the release of [l4C]ACh in a nondepolarising medium. Ouabain (200 μM) increased the release of [14C]ACh evoked by 25 mm‐KCl, but not that evoked by 100μm‐veratrine. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 25 publications
2
24
1
Order By: Relevance
“…Ouabain increases the intrasynaptosomal Na+ concentration by inhibiting the plasma membrane Na+, K+-ATPase (Archibald and White, 1974;Coutinho et al, 1984) and thus consequently causes depolarization (Adam- Vizi and Ligeti, 1984). It has been reported to induce release of ACh from the Auerbach plexus of the gut (Paton et al, 197 1;Vizi, 1977), brain slices (Vizi, 1972), and synaptosomes (Meyer and Cooper, 1981;Vyas and Marchbanks, 1981;AdamVizi and Ligeti, 1984). From the observation that it enhanced the spontaneous nonquantal ACh release from motor nerve terminals (Vyskotil and Illes, 1977;Vizi and Vyskoeil, 1979), an important conclusion could be drawn, namely, that a nonvesicular ACh pool is likely to be involved in the release.…”
Section: Raised Internal Na+ Concentrationmentioning
confidence: 99%
“…Ouabain increases the intrasynaptosomal Na+ concentration by inhibiting the plasma membrane Na+, K+-ATPase (Archibald and White, 1974;Coutinho et al, 1984) and thus consequently causes depolarization (Adam- Vizi and Ligeti, 1984). It has been reported to induce release of ACh from the Auerbach plexus of the gut (Paton et al, 197 1;Vizi, 1977), brain slices (Vizi, 1972), and synaptosomes (Meyer and Cooper, 1981;Vyas and Marchbanks, 1981;AdamVizi and Ligeti, 1984). From the observation that it enhanced the spontaneous nonquantal ACh release from motor nerve terminals (Vyskotil and Illes, 1977;Vizi and Vyskoeil, 1979), an important conclusion could be drawn, namely, that a nonvesicular ACh pool is likely to be involved in the release.…”
Section: Raised Internal Na+ Concentrationmentioning
confidence: 99%
“…It has already been shown that ouabain (Vizi, 1972(Vizi, , 1977Baker & Crawford, 1975;Sandoval, 1980;Meyer & Cooper, 1981;Vyas & Marchbanks, 1981) veratridine (Meyer & Cooper, 1981, Schoffelmeer & Mulder, 1983 are also able to increase transmitter release from different tissues under these conditions. Our aim was to follow not only the change in ACh release but also 86Rb+ distribution.…”
Section: Adam-vizi and E Ligeti Dependence Of[14c]ach Release On mentioning
confidence: 99%
“…Vyas & Marchbanks (1981) suggested that in the presence of extracellular Ca2+ a 'normal', depolarization-induced, Ca2+-dependent release process is produced in synaptosomes by ouabain whereas in the absence of external Ca2+ an unspecific change in membrane permeability independent of depolarization leads to increased transmitter release. Our finding, the clearly similar character of the relationship between membrane potential and ACh release in the presence and absence of external Ca2+, would suggest one principal mechanism operating in both cases.…”
Section: Ouabain and Veratridine: Intracellular Ca2+mentioning
confidence: 99%
See 1 more Smart Citation
“…Several interpretations have been proposed, among them the view that release is a consequence of an increase in the permeability of the membrane, directly associated with the inhibition of Na+-K+-ATPase (Vizi, 1978), or that the increased release is a consequence of depolarization and of a detergent action of ouabain (Vyas & Marchbanks, 1981), or that the opening of (hypothetical) ACh gates is caused by the change in intracellular H+ concentration after the Na+-K+-ATPase had been inhibited (Meyer & Cooper, 1981). Our experiments in which ouabain increased the release of ACh from the innervated diaphragms by 77 % while not affecting that from denervated diaphragms may have important implications regarding the mechanism of the ACh-releasing effect of ouabain.…”
Section: The Content Of Ach In the Diaphragmmentioning
confidence: 99%